Relationship between physical activity and depressive symptoms in stroke survivors: a cross-sectional study of 1,140 individuals - Yihao Wang; Jiali Chen; Yanwei Zou; Mengshu Yang; Xiaoyun Kong; Ling Wang; Jingyuan Xue; Ci Dong (Journal of Rehabilitation Medicine)
Objectives: To investigate the relationship between physical activity and depressive symptoms in stroke survivors.